Mejora de la toma de decisiones en ciclo de ventas del subsistema comercial de servicios en una empresa de IT - Vanegas, Diego Armando; Tarazona Bermudez, Giovanny Mauricio; Rodriguez Rojas, Luz Andrea (Revista Científica, 2020)
The high volume of data, the processing time and the visualization of information are problems that organizations in the technology sector, particularly the commercial subsystem, must face today. In this research, a model for decision-making based on the interaction of criteria and stages of the sales cycle was developed. A specialized business intelligence tool was used that facilitated the handling of large volumes of data, its processing and the visualization of information. Among the results obtained, a significant reduction was found in the time of obtaining the information, it went from hours to minutes.